2006
DOI: 10.1039/b511645g
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle sampling by electrowetting-actuated droplet sweeping

Abstract: This paper describes a new microparticle sampler where particles can be efficiently swept from a solid surface and sampled into a liquid medium using moving droplets actuated by the electrowetting principle. We successfully demonstrate that super hydrophilic (2 microm and 7.9 microm diameter glass beads of about 14 degrees contact angle), intermediate hydrophilic (7.5 microm diameter polystyrene beads of about 70 degrees contact angle), and super hydrophobic (7.9 microm diameter Teflon-coated glass beads and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 25 publications
1
62
0
Order By: Relevance
“…Demonstrated applications of digital microfluidics include the on-chip detection of explosives such as commercial-grade 2,4,6-trinitrotoluene (TNT) and pure 2,4-dinitrotoluene [6], automated on-chip measurement of airborne particulate matter [21], [22], and colorimetric assays [7]. Measured performance metrics for such colorimetric assays have been reported in prior work, e.g., [2], [7].…”
Section: B Digital Microfluidicsmentioning
confidence: 99%
“…Demonstrated applications of digital microfluidics include the on-chip detection of explosives such as commercial-grade 2,4,6-trinitrotoluene (TNT) and pure 2,4-dinitrotoluene [6], automated on-chip measurement of airborne particulate matter [21], [22], and colorimetric assays [7]. Measured performance metrics for such colorimetric assays have been reported in prior work, e.g., [2], [7].…”
Section: B Digital Microfluidicsmentioning
confidence: 99%
“…Mainly diffusive flow, but with contribution from convective and Marangoni flow, further transports the drug molecules through the buffer liquid to the QCM surface. In competition with the immobilized antigens, the drug molecules react with the antibodies (6). The formed drug-Ab complexes release from the sensor surface (7), leading to a decrease in surface-mass and consequently a measurable increase in resonance frequency of the QCM (8).…”
Section: Sensor Design and Measurement Principlementioning
confidence: 99%
“…Desai et al 5 demonstrated airborne particle sampling with a liquid meniscus interface with DEP driven particle capture through the airliquid interface. Recently, Zhao et al 6 showed particle trapping with EWOD droplet sweeping.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of environmental monitoring, automated on-chip measurement of airborne particulate matter has been proposed using a scanning droplet method [57,58]. Target applications include quasi real time sampling of airborne contaminants and bioagents, and detection and quantification of nitroaromatic explosive particles.…”
Section: Emerging Applicationsmentioning
confidence: 99%